Foreign bidders going once, going twice...: Protection in government procurement auctions - Matthew T. Cole; Ronald B. Davies (University College Dublin, UCD School of Economics, 2014)
Until recently, government procurement bidding processes have generally favored domestic firms by awarding the contract to a domestic firm even if a foreign firm tenders a lower bid, so long as the difference between the two is sufficiently small. This has been replaced by an agreement abolishing this practice. However, the presence of other trade barriers, such as tariffs, can continue to disadvantage foreign firms. We analyze the bidding strategies in such a game and show that when domestic profits are valued, tariffs will be used to discriminate against foreign firms. Furthermore, we find that optimal tariffs can be more protectionist than the optimal price preference, resulting in lower expected domestic welfare and total surplus.
Keywords: F13; H57; F12; 330; Government Procurement; Tariffs; Price Preference